Comparison of Researcher’s Reference Management Software: Refworks, Mendeley, and EndNote - Basak, Sujit Kumar (Journal of Economics and Behavioral Studies, 2014)
This paper aimed to present a comparison of researcher’s reference management software such as RefWorks, Mendeley, and EndNote. This aim was achieved by comparing three software. The main results of this paper were concluded by comparing three software based on the experiment. The novelty of this paper is the comparison of researcher’s reference management software and it has showed that Mendeley reference management software can import more data from the Google Scholar for researchers. This finding could help to know researchers to use the reference management software.